Low velocity impact characterisations of flax/kenaf/glass fibre hybrid composites - Razali, Noorshazlin (2021)
Kenaf is widely used in Malaysia. Flax was hybridized with kenaf to improve the kenaf composites properties. Glass fibre has been chosen to hybrid with flax/kenaf composites to study their impact damage behaviour. All specimens were fabricated using hand lay-up technique. Flax/kenaf specimens were used for physical, mechanical and thermal test. The result shows that the mechanical properties are improve when the hybrid specimen was used as test specimens. From the entire test, hybrid composites of flax BL150 fibre and kenaf fibre show the highest tensile and flexural properties for each test. The thermal properties will be increased when the hybrid specimen was used as test specimens. From the results achieved, the best kenaf/flax composites were selected to hybrid with glass fibre for low velocity impact test. The motivation for this work is to identify the low velocity impact damage by changes in the type of materials and impact energy level. Different energy levels used were 15J, 30J, 45J, 60J, 75J and 90J. The impact energy absorption, penetration behaviour, composites failure and impact force were discussed. The specimen was attached to acoustic emission sensor while doing the impact test. The correlation between the impacted specimens and types of materials was discussed. A general trend was observed which indicates that as height increase, the energy absorbed also increases. Impact damage was found to be in the form of fibre cracking, fibre breakage and matrix cracking. Results from this research can be used as a reference in designing the structure of aircraft applications and in developing a better understanding of the test methods used to characterise impact behaviour. The research later was end up with the result from post impact.